Bottom-charmed baryons in a nonrelativistic quark model - Qing-Fu Song; Qi-Fang Lü; Atsushi Hosaka (European Physical Journal C: Particles and Fields, 2024)
Abstract In this work, we study the low-lying mass spectra for bottom-charmed baryons in a nonrelativistic quark model by solving the three-body Schrödinger equation. The lowest $$Ξ _{bc}$$ Ξ bc , $$Ξ _{bc}^′ $$ Ξ bc ′ , $$Ω _{bc}$$ Ω bc , and $$Ω _{bc}^′ $$ Ω bc ′ states are predicted to be about 6979, 6953, 7109, and 7092 MeV, respectively. Also, the strong decays for the low-lying excited states are investigated. Our results indicate that some of $$λ $$ λ -mode P-wave bottom-charmed baryons are relatively narrow, which can be searched for in future experiments. For the low-lying $$ρ $$ ρ -mode and $$ρ -λ $$ ρ - λ hybrid states, their strong decays are highly suppressed and they can survive as extremely narrow states. Moreover, the mass spectra and strong decays for bottom-charmed baryons preserve the heavy quark symmetry well. We hope our calculations can provide helpful information for further experimental and theoretical researches.